SPATIAL FUTURES: ASPIRATIONS AND ACTIONS REGARDING FORM AND SPATIAL CHANGE IN JOHANNESBURG - Todes, Alison; Charlton, Sarah; Rubin, Margot; Appelbaum, Alexandra; Harrison, Philip (My University, 2016)
Addressing the racially divided, sprawling and socially inequitable spatial form of South African cities has been key to strategic spatial planning and urban spatial frameworks in South African cities, including in Johannesburg. These ideas were included in the Johannesburg 2006 Growth and Development Strategy (GDS), and in the 2011 GDS, which focused more strongly on resilience, but making strong links to spatial form. They have also been a consistent element of various rounds of Johannesburg Spatial Development Frameworks (SDFs). However, despite several of these concerns being embodied in national urban and city policies, objectives to restructure cities spatially have proven to be very difficult to achieve, and there is a growing frustration and questioning of whether some of these objectives are still appropriate. At the same time, the urban restructuring agenda, and the areas that spatial policy addresses have been constrained in practice, and there are several gaps and silences in the issues that are addressed. This paper provides a discussion of the choices, tensions, and trade-offs facing spatial policy in Johannesburg. It considers whether the policy objectives expressed in existing spatial policies (including the Johannesburg GDS and SDF) are still relevant, and address key spatial dynamics and issues. It does this by exploring several key areas of debate around the spatial form of cities and spatial policy internationally, examining how they manifest in Johannesburg, and highlighting these choices, tensions and trade-offs. It recognises, as a starting point, that while urban spatial policies have some power to shape spatial change, spatial trends and dynamics occur in a complex environment, where there are many drivers and shapers of spatial change. As emphasised in the position paper on ‘Strategic Planning in a Turbulent and Uncertain Context’, spatial policies that hope to influence spatial change need to understand the (shifting) key trends and drivers that affect space, including demographic, economic and social patterns that influence the demand for space. There are many examples of spatial plans which missed key trends, vastly over- or under- estimated population growth, and consequently planned for spatial forms which proved to be inappropriate. The spatial form of cities is also shaped by markets of various forms. Planning may attempt to engage with and regulate or direct these markets in the interests of its social and spatial goals and objectives, but it does not have completely free reign. Further, there are frequently disjunctures between strategic spatial planning and implementation, reflecting limits in terms of capacity, political will, institutional cooperation/integration and other factors. Finally, city spatial policies do not occur in isolation, nor do spatial policies necessarily have the power desired by planners. Spatial change and spatial form is critically affected by infrastructural investments, particularly in relation to transport (roads, transit systems), which are frequently follow a different planning process and logic (UN-Habitat, 2009). Likewise, differences between spheres of government and sectoral departments with power to invest in the built environment are also key to the disjunctures between spatial plans and outcomes. The emphasis on housing delivery on scale, along with cheaper land on the periphery, has undermined spatial policies towards urban compaction both internationally (Buckley et al., 2016) and in South Africa (Charlton, 2014). The recent international emphasis on ‘mega- projects’ is often driven by the private sector (such as major gated estates), but also by parts of the public sector (for example eThekwini’s airport). It is also influencing spatial change, bypassing spatial plans or forcing their adaptation (Shatkin, 2008; Robbins et al, 2015; Todes, 2014). This paper explores several key points of focus and debate affecting the spatial futures of cities, particularly in relation to Johannesburg. It draws out the key choices, tensions and trade-offs in these areas, and their implications for future spatial planning in Johannesburg. These include: • The debate over the creation of a more compact urban form, versus expanding and sprawling cities, including the discussion of new cities and satellite cities. Sustainability and resilience as key discourses and their implications for urban spatial form, and the role of transport and mobility will be considered in this context. Understandings of densification, how it is encouraged and managed will also be discussed. • Trends towards social exclusion versus arguments for spatial justice and the right to the city. This discussion considers trends towards privatised and splintered urbanism, gated communities, gentrification, and safety and security as a driver. It also discusses other dimensions of exclusion/inclusion—race, gender and the question of migrant spaces, and policies on socio-spatial integration. • Processes of spatial change in poor neighbourhoods, and initiatives to improve conditions there, including upgrading informal settlements, the growth of informal trade, addressing backyard housing. • Relationships between space and economic development, including the dynamics of growth and decline across the city, debates over promoting development on the periphery versus existing areas of agglomeration, and initiatives to promote economic development in townships. • City-region and multi-scalar governance, including the extent to which metropolitan governance addresses competing tensions and interests across the city, cross-border issues, and disjunctures and tensions between spheres of government.
A report for Group Strategy, Policy Coordination and Relations, City of Johannesburg
Keywords: spatial futures; City of Johannesburg; Urban spatial form; Densification; Social exclusion; spatial justice; spatial change; multi-scalar governance; economic development; GDS